2016
DOI: 10.1187/cbe.15-07-0163
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Student Gains from Undergraduate Research Experiences at a Hispanic-Serving Institution

Abstract: When factors relevant to student gains from undergraduate research were examined, results revealed that students who reported receiving higher-quality mentorship, spending more hours caring for dependents, and receiving more programmatic resources experienced significantly greater gains in science competency, personal growth, and skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 42 publications
2
59
0
Order By: Relevance
“…[20][21][22] Interestingly, Daniels et al showed that mentoring is more significant and efficient to promote students personal, and skill gains than the time spent doing research. 23 Our results support these findings; although time spent in research is important, mentorship is key to develop students' confidence, competence and performance. Participants' gained confidence in themselves from interactions with mentors and, due to this interaction, they report that their future career plans and educational possibilities in science have broadened.…”
Section: Discussionsupporting
confidence: 79%
“…[20][21][22] Interestingly, Daniels et al showed that mentoring is more significant and efficient to promote students personal, and skill gains than the time spent doing research. 23 Our results support these findings; although time spent in research is important, mentorship is key to develop students' confidence, competence and performance. Participants' gained confidence in themselves from interactions with mentors and, due to this interaction, they report that their future career plans and educational possibilities in science have broadened.…”
Section: Discussionsupporting
confidence: 79%
“…Both were actively involved, as they were passionate about the scientific field of molecular biology. In addition, highquality mentorship could result in more efficient project achievements [12].…”
Section: Resultsmentioning
confidence: 99%
“…The human hepatoma cell line Huh7 cells [11][12] were cultured in Dulbecco's modified Eagle's medium (DMEM) (Thermo Scientific, Hudson, NH) supplemented with 10% fetal bovine serum (Invitrogen Corporation/Gibco, CA), 100 U/ml penicillin and streptomycin 100 μg/ml (American Type Culture Collection, Manassas, VA), and non-essential amino acids (Invitrogen Corporation/Gibco, CA). All cells were passaged at 80-90% confluence for long-term maintenance in culture.…”
Section: Cell Culturementioning
confidence: 99%
“…While prior studies show the benefits of early exposure to research through intervention programs [17,22], the advantages vary for minorities since they are less likely to participate in such research-related experiences [23]. Fewer black, Latino, and first-generation college students have engaged in research as undergraduates, as compared to white and Asian students [23].…”
Section: Variables Influencing Outcomes Of Research Experiences For Mmentioning
confidence: 99%